Genome-wide analysis of PRR gene family uncovers their roles in circadian rhythmic changes and response to drought stress in Gossypium hirsutum L. - Wang,Jingjing; Du,Zhaohai; Huo,Xuehan; Zhou,Juan; Chen,Yu; Zhang,Jingxia; Pan,Ao; Wang,Xiaoyang; Wang,Furong; Zhang,Jun (PeerJ, 2020)
Background The circadian clock not only participates in regulating various stages of plant growth, development and metabolism, but confers plant environmental adaptability to stress such as drought. Pseudo-Response Regulators (PRRs) are important component of the central oscillator (the core of circadian clock) and play a significant role in plant photoperiod pathway. However, no systematical study about this gene family has been performed in cotton. Methods PRR genes were identified in diploid and tetraploid cotton using bioinformatics methods to investigate their homology, duplication and evolution relationship. Differential gene expression, KEGG enrichment analysis and qRT-PCR were conducted to analyze PRR gene expression patterns under diurnal changes and their response to drought stress. Results A total of 44 PRR family members were identified in four Gossypium species, with 16 in G. hirsutum, 10 in G. raimondii, and nine in G. barbadense as well as in G. arboreum. Phylogenetic analysis indicated that PRR proteins were divided into five subfamilies and whole genome duplication or segmental duplication contributed to the expansion of Gossypium PRR gene family. Gene structure analysis revealed that members in the same clade are similar, and multiple cis-elements related to light and drought stress response were enriched in the promoters of GhPRR genes. qRT-PCR results showed that GhPRR genes transcripts presented four expression peaks (6 h, 9 h, 12 h, 15 h) during 24 h and form obvious rhythmic expression trend. Transcriptome data with PEG treatment, along with qRT-PCR verification suggested that members of clade III (GhPRR5a, b, d) and clade V (GhPRR3a and GhPRR3c) may be involved in drought response. This study provides an insight into understanding the function of PRR genes in circadian rhythm and in response to drought stress in cotton.
Keywords: Gossypium hirsutum; PRR family; Photoperiod; Circadian rhythm; Drought response